Game engine toolset development - Wihlidal, Graham; ebrary, Inc. (Boston, MA : Thomson Course Technology, 2006)
"Developing a core foundation of tools that can be used from one project to the next is a skill that can save a tremendous amount of time and money. Although toolset development is a broad topic, this book provides you with a comprehensive set of skills designed to aid you in the development of game engine tools. Utilizing the C# language and the Microsoft .NET 2.0 Framework, you will study toolset development methodologies that will help you successfully complete your project while significantly reducing the time required for the construction phase. If you have a working knowledge of C# and the .NET Framework, then you have everything you need to begin creating your own game engine tools."
Includes "Bonus Web sites chapters on web site"--P. xvi.
Includes index.
Electronic reproduction.
Keywords: Direct3D.; DirectX; C# (Computer program language); Computer games -- Design and construction; Computer games -- Programming; Microsoft .NET.; Three-dimensional display systems -- Programming; Visual programming (Computer science); Electronic books